The Southwest UK Burns Network (SWUK) experience of electronic cigarette explosions and review of literature. Issue 4 (June 2017) - Arnaout, A.; Khashaba, H.; Dobbs, T.; Dewi, F.; Pope-Jones, S.; Sack, A.; Estela, C.; Nguyen, D.
Highlights: Multi-centre review of e-cigarette explosions in the Southwest Burns Network. Increasing risk of spontaneous explosion of the lithium ion battery in electronic cigarettes. Lithium ions leak following a breach in the battery, first aid with mineral oil use is advocated. Restrictions on e-cigarette import to ensure they meet UK Standard Specifications. Restrictions on use of e-cigarettes in high risk areas; aviation, healthcare, public transport. Abstract: Introduction: Since the introduction of e-cigarettes to the UK market in 2007 their popularity amongst young adults has significantly increased. These lithium-ion powered devices remain unregulated by the Standards Agency and as a result burns centres across the world have seen an increasing number of patients presenting with significant burns, resulting from poor quality batteries that appear to be liable to explode when over-heated, over-charged or incorrectly stored. Methods: Retrospective and perspective review of all e-cigarette related burns presenting to the Southwest Burns Network; South Wales Burns Centre (Morriston Hospital) or to Bristol burns centre (Southmead Hospital) between Oct 15–July 16, followed by a review of available literature performed and eligible papers identified using PRISMA 2009 Checklist. Results: South Wales Burns Centre (Morriston Hospital) (N = 5), Bristol burns centre (Southmead Hospital) (N = 7). 92% of injuries were seen in male patients with a mean age of 34.58 (±12.7). The mean TSBA sustained 2.54% of mixed depth, most common anatomical area is the thigh 83% (n = 10) with a mean 23.1(±5) days to heal with conservative management. The literature search yielded 3 case series (Colaianni et al., 2016; Kumetz et al., 2016; Nicoll et al., 2016) [8, 9, 12] and 4 case reports (Jablow and Sexton, 2015; Harrison and Hicklin, 2016; Walsh et al., 2016; Shastry and Langdorf, 2016) [6, 7, 10, 11]. We compare our findings with the published studies. Conclusion: The import and sale of e-cigarettes remains unrestricted. This increases the risk of devices being available in the UK market that do not meet the British Standard Specification, potentially increasing their risk of causing fire and exploding. Consumers should be made aware of this risk, and advised of adequate charging and storage procedures. In case lithium ion compounds leak following a breach in the battery, first aid with mineral oil use is advocated to avoid a further chemical reaction.